PENGARUH PENGGUNAAN APLIKASI WATTPAD TERHADAP PENINGKATAN KEMAMPUAN LITERASI PEMUSTAKA UPT PERPUSTAKAAN UIN RADEN FATAH PALEMBANG - Imelda Putri Damayanti; Budhi Santoso; Herlina Herlina (Perpustakaan Nasional RI, 2021)
This study discusses influence of the use of Wattpad application on literacy ability improvement of UIN Raden Fatah Palembang library users. The purpose of this study is to find out what is the influence of the use of Wattpad application on literacy skill improvement of UIN Raden Fatah Palembang library users. This research is of quantitative descriptive research. The population of this study was library visitor in August 2020 - August 2021. The sample in this study was determined using Slovin formula with an error rate of 10%, so the sample in this study was 100 users who were users of Wattpad application. The results of respondents' answers calculation indicate that the average total value of variable X can be categorized as high because it was on an interval scale of 3.4 - 4.2, which was 3.98. And the results of respondents' answers calculation show that the average total value of variable Y can be categorized as high because it was on a scale of 3.4 - 4.2, which was 3.84. And on the T test, it was found that there was a positive effect of using Wattpad application on literacy ability of UIN Raden Fatah Palembang library users with the results of the calculation of rcount 7.035 rtable 1.98447, which stated that there was an effect of using Wattpad application on literacy ability.